2016
DOI: 10.35119/asjoo.v16i1.342
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and histopathological correlation: A study on 334 eyes with retinoblastoma from Vietnam

Abstract: Purpose: To elucidate the clinical features which predict high-risk histopathological factors for subsequent metastatic disease as well as to report the incidence of these high-risk histopathological factors in a cohort of Asian patients with retinoblastoma. Design: A retrospective and non-randomized sequential cases series. Methods: A retrospective study was done on 334 eyes with retinoblastoma at Vietnam National Institute of Ophthalmology during a 10 year period (January 2004 – December 2013). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
1
1
Order By: Relevance
“…tion and survival outcomes of children affected by RB vary widely across studies around the world. 1 In our study, the median age of onset was 18.9 months (range: 1-63 months), which was older than some previous studies in Japan (13.5 13 Older age was also found in some studies in other countries, including Malaysia (24.2 months), India (29 months), Ghana (36 months), and Kenya (37.5 months). 14 The mean age in the bilateral RB group was usually younger, although some studies from the United States and India showed a higher incidence of unilateral disease than bilateral disease.…”
Section: F I G U R E 2 Kaplan-meier Estimates Of Progression-free Sur...contrasting
confidence: 45%
See 1 more Smart Citation
“…tion and survival outcomes of children affected by RB vary widely across studies around the world. 1 In our study, the median age of onset was 18.9 months (range: 1-63 months), which was older than some previous studies in Japan (13.5 13 Older age was also found in some studies in other countries, including Malaysia (24.2 months), India (29 months), Ghana (36 months), and Kenya (37.5 months). 14 The mean age in the bilateral RB group was usually younger, although some studies from the United States and India showed a higher incidence of unilateral disease than bilateral disease.…”
Section: F I G U R E 2 Kaplan-meier Estimates Of Progression-free Sur...contrasting
confidence: 45%
“…In our study, the median age of onset was 18.9 months (range: 1–63 months), which was older than some previous studies in Japan (13.5 months), Colombia (8.7 months), and Thailand (8 months) 11,12 . However, an older age of onset has been reported by Nguyen et al., with 334 RB eyes with primary removed from 2004 to 2013 at the National Eye Hospital in Vietnam, the mean age was 25.4 months 13 . Older age was also found in some studies in other countries, including Malaysia (24.2 months), India (29 months), Ghana (36 months), and Kenya (37.5 months) 14 .…”
Section: Discussionmentioning
confidence: 62%